The Dynamics of Legal Protection For Notaries In Performing Notarial Duties - Rachel Gunawan; Benny Djaja; Maman Sudirman (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
This study examines the problem of the dynamics of legal protection related to the weaknesses of the dual position regulation of Notaries in the Law on Notary Positions, which creates legal uncertainty and potential conflicts of interest. First, the inconsistency between Article 11 paragraph (1) which allows Notaries to take leave while serving as state officials with other articles that require total dismissal creates legal confusion. Differences in interpretation regarding "resigning" and "leaving" cause ambiguity regarding the legal status of Notaries, which can affect legal compliance and potentially lead to abuse. Second, the use of the name and protocol of Notaries who are on leave by their replacements increases the risk of conflicts of interest and public misunderstanding. The public can misunderstand the legal responsibilities between Notaries who are on leave and their replacements, especially if violations or errors occur during the leave period. Therefore, regulatory revisions are needed to ensure legal clarity, professional integrity, and protection for parties involved in notarial services.